(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
بينت الدراسة أن الكثافة الظاهرية للتربة تزداد مع زيادة الضغط والرطوبة أثناء الانضغاط وكان معدل الزيادة الأكبر في العمق 5-25 سم حيث بلغت الزيادة كمتوسط لعامين 0.33 غ/سم3 عند الضغط ب310.88 كيلوباسكال ومتوسط الرطوبة أثناء الضغط 17.02 % ( تعادل 66.2% من متوسط السعة الحقلية للتربة )مقارنة بالمعاملة بدون ضغط . كما أن حجم المسامات أكبر من 50 ميكرون انخفض عند نفس الضغط السابق ومتوسط الرطوبة السابقة في العمق 5-25 سم بمقدار 12.87% . وانخفض حجم المسامات أكبر من 10 ميكرون بمقدار 14.08 % كمتوسط لعامين مقارنة مع المعاملة دون ضغط. وأن معامل التوصيل الهيدروليكي للتربة المشبعة انخفض في العمق 5-25 سم حيث بمقدار 26.3 مرة كمتوسط لعامين عند الضغط 310.88 كيلوباسكال ومتوسط الرطوبة أثناء الضغط 17.02 % مقارنة بالمعاملة دون ضغط . كما بينت الدراسة أن الضغط يجب أن لا يزيد عن 100 كيلوباسكال عند رطوبة أثناء الانضغاط تعادل 58% من السعة الحقلية للتربة أو 75 كيلوباسكال عند رطوبة 80% من السعة الحقلية للتربة وان لاتزيد حمولة العجلة عن 5 كيلونيوتن عند رطوبة 58% من السعة الحقلية أو 3.5 كيلونيوتن عند رطوبة تعادل 80 % من السعة الحقلية للتربة . حتى لايحصل انخفاض معنوي للإنتاج . The study has shown that the apparent bulk density of soil increases with the increase of compression and moisture during press. The maximum rate of increase in depth was 5 – 25 cm that amounted in average in two years 0.33g/cm3 at compression by 310.88 kilopascal , and moisture average at compression by 17.02% (equal to 66.2% of the field capacity average of the soil) in comparison with the non existence of compression. Also, the size of the pores bigger than 50 microns decreased at the same above compression and above moisture in depth of 5 – 25 cm by 12.87%. The size of pores bigger than 10 microns decreased by 14.08% in two years average in comparison with the non existence of compression. Hydraulic connection coefficient of the saturated soil in depth of 5 – 25 cm decreased by 26.3 times in two years average at compression of 310.88 kilopascals and moisture average at compression by 17.02% in comparison with the non existence of pressure. The study has shown as well that the compression should not exceed 100 kilopascals with moisture at compression equal to 58% of the field capacity of soil or 75 kilopascals with moisture of 80% of the field capacity of soil, and the wheel load should not exceed 5 kilo newtons with moisture of 58% of field capacity or 3.5 kilo newtons with moisture equal to 80% of the field capacity of the soil; in order to avoid serious decrease in production.